Unveiling the Potential of Circular Economy in Cattle Waste Management for Achieving Sustainable and Green Growth - Alina Azzara; I Putu Gede Didik Widiarta; Muhammad Fahrul; Rahmat Budi Ramadhani (SEAS (Sustainable Environment Agricultural Science), 2025)
The cattle industry is a key component of the global agricultural economy, and faces significant challenges related to waste management and environmental sustainability. In response to growing concerns over greenhouse gas emissions and resource depletion, this study investigates the potential of circular economy (CE) principles in transforming cattle waste management practices to promote a green economy and sustainable development. This study employs a comprehensive literature review methodology to analyze various strategies for implementing CE approaches in the cattle sector, synthesizing findings from relevant publications. The study aims to identify effective methods for reducing methane emissions, enhancing resource utilization efficiency through biogas and organic fertilizer production, and fostering cross-sectoral integration between livestock and agricultural operations. The results highlight the potential for CE implementation to substantially reduce the environmental footprint of cattle farming while creating new revenue streams. Key challenges include the need for technological infrastructure investment, supportive government policies, and enhanced farmer education. The study concludes that strategic policy interventions are essential to incentivize the adoption of CE practices, promote technological innovation, and ensure the long-term sustainability of the cattle industry. The findings provide actionable insights for policymakers, industry stakeholders, and researchers to foster the transition toward a more resource-efficient and environmentally responsible cattle sector.